Anthropometric-based customization of head-related transfer functions using Isomap in the horizontal plane - Grijalva, Felipe; Martini, Luiz; Goldenstein, Siome; Florencio, Dinei (ICASSP'14, 2014)
In this paper, we introduce a new anthropometric-based method for customizing of Head-Related Transfer Functions (HRTF) in the horizontal plane. The method uses Isomap, artificial neural networks (ANN), and a neighborhood-based reconstruction procedure. We first modify Isomap’s graph construction step to emphasizes the individuality of HRTFs and perform a customized nonlinear dimensionality reduction of the HTRFs. We then use an ANN to model the nonlinear relationship between anthropometric features and our low-dimensional HRTFs. Finally, we use a neighborhood-based reconstruction approach to reconstruct the HRTF from the estimated low-dimensional version. Simulations show that our approach performs better than PCA and confirm that Isomap is capable of discovering the underlying nonlinear relationships of sound perception.